Gm_Realization of Controlled_Gain Current Follower Transconductance Amplifier - Worapong Tangsrirat (My University, 2013)
This paper describes the conception of the current follower transconductance amplifier (CFTA) with electronically and linearly current tunable. The newly modified element is realized based on the use of transconductance cells ( G m s ) as core circuits. The advantage of this element is that the current transfer ratios ( i z / i p and i x / i z ) can be tuned electronically and linearly by adjusting external DC bias currents. The circuit is designed and analyzed in 0.35 μ m TSMC CMOS technology. Simulation results for the circuit with ±1.25 V supply voltages show that it consumes only 0.43 mw quiescent power with 70 MHz bandwidth. As an application example, a current‐mode KHN biquad filter is designed and simulated.
Keywords: Operational transconductance amplifier; Realization (probability); Transconductance; Analog and Mixed-Signal Circuit Design